Bank stock returns and macroeconomic variables: Empirical evidence from selected ASEAN countries - Mohammed, Ahmed Jasim (2015)
The aim of this study is to examine the effect of macroeconomic variables on bank stock returns in ASEAN. The panel data were retrieved from the DataStream and World Bank data archive, consisting of 58 banks from six countries (Malaysia, Indonesia, Singapore, Thailand, Philippines, and Vietnam) for the period 2004 to 2014. The bank stock return index is used as a proxy for bank stock return while proxies for macroeconomic variables are money supply, interest rate, inflation, and foreign exchange rate. By applying pooled OLS regression analysis, the results show that money supply has negative impact on bank stock returns, indicating that changes in money supply is a major signal for change in stock price because it has a direct influence on stock market and an indirect influence on bond market based on the adjustment of interest rates. Inflation also has negative significant influence on bank stock returns, implying that negative inflation –real activity induced the relationship through the money demand theory and the quantity theory of money. Foreign exchange rate has a positive significance influence on bank stock returns, indicating that the foreign exchange exposures of ASEAN banks have influenced their stock returns since most part of the stock returns are sensitive to the changes in exchange rates during the periods. Meanwhile, interest rate is insignificant with bank stock returns, implying that interest rate sensitivity does not exert a significant impact on the common stock of the banks, which could be caused by the effect of wealth distribution triggered by unexpected inflation when banks hold nominal assets and nominal liabilities. It is recommended that ASEAN banks should involve in various off-balance sheet activities and implement effective and efficient approaches of risk management which reduce their exposure to fluctuations in macroeconomic factors